The management of accidental perineal injuries in pediatric females: Retrospective review at a single institution - Ellen M. Encisco; Krithika Sundaram; Neil L. McNinch; Mark L. Wulkan; Justin T. Huntington; Nathan P. Heinzerling; Joseph A. Iocono (Elsevier, 2023)
Background: The indications for operative management of pediatric perineal injuries are debated. We aimed to investigate our institution's experience with perineal injuries in girls and identify factors for which patients require examination under anesthesia (EUA). Methods: All female pediatric patients presenting to our institution June 2015-2021 with an isolated perineal injury were reviewed. Demographics, symptoms, exam findings, Genitourinary Injury Score (GIS), and management strategy were recorded and analyzed. Patients were divided based on level of intervention - bedside examination without sedation, Emergency Department (ED) exam with sedation, or EUA. Results: In total, 202 patients with a median age of 6 years were analyzed. Bleeding was reported most frequently by patients and families (90.1%), but only 27.2% of patients had bleeding noted on ED exam. Over half of patients (n = 110, 54.5%) were managed nonoperatively; the remaining 92 (45.5%) underwent EUA. The majority of patients (n = 150, 74.3%) had a GIS of I. EUA patients had a higher estimated median total injury size (2.5 (1.5-3.5) cm vs 1.0 (0.5-1.5) cm, p < 0.001), higher percentage of active bleeding (53.3% vs. 4.8%), and higher GIS (≥ II). No one discharged from the ED required operative intervention at a later time. Conclusion: Although further prospective evaluation is required, our investigation suggests the majority of patients presenting with perineal injuries can be managed in the emergency department, but operative intervention should be considered for patients presenting with active bleeding on physical exam, laceration or hematoma > 2 cm, or GIS ≥ II.